2010
DOI: 10.1080/13576500902958871
|View full text |Cite
|
Sign up to set email alerts
|

Degree versus direction: A comparison of four handedness classification schemes through the investigation of lateralised semantic priming

Abstract: Four classification systems were examined using lateralised semantic priming in order to investigate whether degree or direction of handedness better captures the pattern of lateralised semantic priming. A total of 85 participants completed a lateralised semantic priming task and three handedness questionnaires. The classification systems tested were: (1) the traditional right- vs left-handed (RHs vs LHs); (2) a four-factor model of strong and weak right- and left-handers (SRHs, WRHs, SLHs, WLHs); (3) strong- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…However, a growing body of evidence suggests that handedness may provide some useful insights into individual differences in behavior (e.g., Wright et al, 2004; Kaploun and Abeare, 2010). Early research tended to examine differences between left- and right-handers and often found contradictory influences on behavior, although more recently there has been a move toward examining how handedness categories may influence the relationship with other variables (Beratis et al, 2011; Wright and Hardie, 2012; Hardie and Wright, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a growing body of evidence suggests that handedness may provide some useful insights into individual differences in behavior (e.g., Wright et al, 2004; Kaploun and Abeare, 2010). Early research tended to examine differences between left- and right-handers and often found contradictory influences on behavior, although more recently there has been a move toward examining how handedness categories may influence the relationship with other variables (Beratis et al, 2011; Wright and Hardie, 2012; Hardie and Wright, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, on the basis of an item response theory evaluation of one of the major handedness questionnaires (Oldfield’s, 1971; Edinburgh Handedness Inventory, EHI), Büsch et al (2010) strongly argue that only two classes of response emerge – left- and right-handed. Other researchers have argued that the most appropriate way to measure handedness is to examine a tripartite model – covering consistent-left, consistent-right and mixed-handers, based on factor-analysis (Peters and Murphy, 1992), neuroimaging (e.g., Knecht et al, 2000; Kirveskari et al, 2006) and behavioral studies (Kaploun and Abeare, 2010). Finally, recent work in this area combines both direction and degree; Lyle et al (2012a) found differences between consistency groups within handedness categories.…”
Section: Introductionmentioning
confidence: 99%
“…Disparate findings from large-scale studies of functional brain lateralization and 20 handedness have resulted in revived discussions -at least from within the community of laterality 21 researchers -on the use of the EHI and other handedness inventories. One result of these renewed 22 discussions is a "degree vs. direction" approach, where subjects are classed not into binary 23 directional categories (right-vs. left-hander), but into ordinal categories reflecting degree of 24 handedness, such as strong right-handed, mixed-handed, weak left-handed, etc., prior to analysis 25 (Gonzalez & Goodale, 2009;Kaploun & Abeare, 2010;Newman et al, 2014;Pritchard et al, 26 2013;Somers et al, 2015). This approach has led to some improvements, most notably in linking 27 variability in left-handers' hand performance, which is generally lacking in right-handers, to 28 similar variability in activation patterns in the brain (Christman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Για παράδειγμα, άτομα με ισχυρή δεξιοχειρία δε θα προτιμήσουν το αριστερό χέρι σε εργασίες που γίνονται με το ένα χέρι και απαιτούν δεξιοτεχνία (Brown et al, 2006). Βάσει ενός γενικού ορισμού η προτίμηση χεριού ορίζεται ως η σταθερή προτίμηση του ενός χεριού για την εκτέλεση περισσότερο ή λιγότερο επιδέξιων κινήσεων και βασίζεται στην αξιολόγηση της απόδοσης (Millar, 1994), μολονότι μέχρι σήμερα δεν υπάρχει απόλυτη συναίνεση στη βιβλιογραφία τόσο για τον ορισμό όσο και για τον τρόπο μέτρησης (Kaploun & Abeare, 2010). Στη νευροψυχολογία η προτίμηση χεριού είναι το πιο αντιπροσωπευτικό παράδειγμα της εξειδικευμένης λειτουργίας ή δραστηριότητας στη μια πλευρά του σώματος (Βλάχος, 2009) και συχνά χρησιμοποιείται ως έμμεσος δείκτης της εγκεφαλικής πλευρίωσης (Guadalupe et al, 2014˙ van der Elst et al, 2011, ωστόσο η σύνδεση εγκεφαλικής πλευρίωσης και προτίμησης χεριού δεν είναι ισχυρή (Somers et al, 2015).…”
Section: προτίμηση χεριούunclassified
“…Μάλιστα, η μειωμένη έκθεση σε τεστοστερόνη (Witelson & Nowakowski, 1991) και η αυξημένη συχνότητα περιγενετικού τραύματος (Searleman, Porac & Coren, 1989) ίσως επηρεάζουν την ανάπτυξη του εγκεφάλου και οδηγούν σε λιγότερα άριστα εγκεφαλικά δίκτυα που συνεπάγονται μειωμένη χωρική λειτουργία (Somers et al, 2015). Επιπλέον, μέσα στον πληθυσμό των αριστερόχειρων, αναφέρεται μεγάλη διακύμανση όσον αφορά την εγκεφαλική πλευρίωση και εικάζεται πως οι διαφορές στην οργάνωση που έχουν παρατηρηθεί στον εγκέφαλο των αριστερόχειρων ίσως έχει λειτουργικές συνέπειες στις γνωστικές λειτουργίες (Kaploun & Abeare, 2010).…”
Section: αριστεροχειρίαunclassified